Elementary Geometry for College Students (5th Edition)

Published by Brooks Cole
ISBN 10: 1439047901
ISBN 13: 978-1-43904-790-3

Chapter 5 - Review Exercises: 8h

Answer

$x = -6, 3$

Work Step by Step

$\frac{x+7}{2} = \frac{x+2}{x-2}$ $(x+7)(x-2)= 2(x+2)$ $x(x+7)-2(x+7)= 2x+4$ $x^{2} + 7x -2x -14 = 2x +4$ $ x^{2} +5x -14 = 2x +4$ $x^{2} +5x - 14 -2x -4 = 0$ $ x^{2} + 3x - 18 = 0$ $ (x+6)(x-3) = 0$ $x = -6, 3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.